Cellular-based immunotherapies for patients with glioblastoma multiforme - Xu, Xun; Stockhammer, Florian; Schmitt, Michael (Clinical & developmental immunology, 2012)
Treatment of patients with glioblastoma multiforme (GBM) remains to be a challenge with a median survival of 14.6 months following diagnosis. Standard treatment options include surgery, radiation therapy, and systemic chemotherapy with temozolomide. Despite the fact that the brain constitutes an immunoprivileged site, recent observations after immunotherapies with lysate from autologous tumor cells pulsed on dendritic cells (DCs), peptides, protein, messenger RNA, and cytokines suggest an immunological and even clinical response from immunotherapies. Given this plethora of immunomodulatory therapies, this paper gives a structure overview of the state-of-the art in the field. Particular emphasis was also put on immunogenic antigens as potential targets for a more specific stimulation of the immune system against GBM.
Gesehen am 29.10.2018